Troglodrilus jugeti n. sp. (Annelida, Clitellata, Tubificinae), a new stygobiont oligochaete species from south-western Europe - Achurra, Ainara; Chatelliers, Michel Creuze Des; Rodriguez, Pilar (Zootaxa, 2012)
We use a morphological approach focused on characters of the reproductive organs to assess the taxonomic status of thestygobiont oligochaete species Troglodrilus galarzai (Giani and Rodriguez, 1988). After the evaluation of 23 characters,diagnostic differences in the spermathecal vestibule, the penial sac and the penial sheath are observed between northernIberian Peninsula populations and south-eastern France populations. Recent molecular analyses based on mitochondrialgene data have revealed a high genetic variation in T. galarzai. Given that both molecular and morphological data supportthe presence of two species within T. galarzai, we propose the specific status for the French populations under the nameTroglodrilus jugeti n. sp. As a result, the type species of the genus, T. galarzai, is now restricted to the Iberian Peninsula.A possible paleogeographic scenario is hypothesised for the evolution of Troglodrilus during the Para-Tethys regression in the Neogene stage.